KAT6A Acetylation of SMAD3 Regulates Myeloid‐Derived Suppressor Cell Recruitment, Metastasis, and Immunotherapy in Triple‐Negative Breast Cancer. Issue 20 (13th August 2021) - Yu, Bo; Luo, Fei; Sun, Bowen; Liu, Wenxue; Shi, Qiqi; Cheng, Shi‐Yuan; Chen, Ceshi; Chen, Guoqiang; Li, Yanxin; Feng, Haizhong
Abstract: Aberrant SMAD3 activation has been implicated as a driving event in cancer metastasis, yet the underlying mechanisms are still elusive. Here, SMAD3 is identified as a nonhistone substrate of lysine acetyltransferase 6A (KAT6A). The acetylation of SMAD3 at K20 and K117 by KAT6A promotes SMAD3 association with oncogenic chromatin modifier tripartite motif‐containing 24 (TRIM24) and disrupts SMAD3 interaction with tumor suppressor TRIM33. This event in turn promotes KAT6A‐acetylated H3K23‐mediated recruitment of TRIM24–SMAD3 complex to chromatin and thereby increases SMAD3 activation and immune response‐related cytokine expression, leading to enhanced breast cancer stem‐like cell stemness, myeloid‐derived suppressor cell (MDSC) recruitment, and triple‐negative breast cancer (TNBC) metastasis. Inhibiting KAT6A in combination with anti‐PD‐L1 therapy in treating TNBC xenograft‐bearing animals markedly attenuates metastasis and provides a significant survival benefit. Thus, the work presents a KAT6A acetylation‐dependent regulatory mechanism governing SMAD3 oncogenic function and provides insight into how targeting an epigenetic factor with immunotherapies enhances the antimetastasis efficacy. Abstract : TGF‐ β 1 potentiates KAT6A acetylation of SMAD3 at K20 and K117, which promotes SMAD3 association with oncogenic H3K23ac reader tripartite motif‐containing 24 (TRIM24) and thereby increases SMAD3 transcriptional activation. Activated SMAD3 upregulates immune‐related cytokines, leading to enhanced breast cancer stem‐like cell properties, myeloid‐derived suppressor cell (MDSC) recruitment, and triple‐negative breast cancer (TNBC) metastasis. Targeting KAT6A improves the anticancer metastasis efficacy of anti‐PD‐L1 therapy.